1995
DOI: 10.1021/bi00033a014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Activation and Functional Significance of the Lipolysis-Stimulated Receptor. Evidence for a Role as Chylomicron Remnant Receptor

Abstract: In cultured human and rat cells, the lipolysis-stimulated receptor (LSR), when activated by free fatty acids (FFA), mediates the binding of apoprotein B- and apoprotein E-containing lipoproteins and their subsequent internalization and degradation. To better understand the physiological role of LSR, we developed a biochemical assay that optimizes both the activation and binding steps and, thus, allows the estimation of the number of LSR binding sites expressed in the livers of living animals. With this techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…It is generally accepted, however, that for the initial liver recognition of remnants, the so-called "capture step," additional systems are needed. The initial sequestration step was suggested to involve heparan sulfate proteoglycans (5,12), the lipolysis-stimulated receptor (13)(14)(15), a TG-rich lipoprotein receptor (16,17), the asialoglycoprotein receptor (18), LPL (19), and/or hepatic lipase (20), while we also provided evidence for a specific remnant receptor (21)(22)(23) to function as an initial recognition site for remnants. However, the removal pathways of chylomicrons and their remnants remain complex, and the precise mechanism of recognition is still unclear and under debate (1-3).…”
mentioning
confidence: 56%
“…It is generally accepted, however, that for the initial liver recognition of remnants, the so-called "capture step," additional systems are needed. The initial sequestration step was suggested to involve heparan sulfate proteoglycans (5,12), the lipolysis-stimulated receptor (13)(14)(15), a TG-rich lipoprotein receptor (16,17), the asialoglycoprotein receptor (18), LPL (19), and/or hepatic lipase (20), while we also provided evidence for a specific remnant receptor (21)(22)(23) to function as an initial recognition site for remnants. However, the removal pathways of chylomicrons and their remnants remain complex, and the precise mechanism of recognition is still unclear and under debate (1-3).…”
mentioning
confidence: 56%
“…Of particular relevance to our study, Mann et al (25) reported that, compared with apoC-III 1 or apoC-III 0 , apoC-III 2 is a less effective inhibitor of VLDL uptake by the hepatic LSR. The LSR has been proposed as a rate-limiting factor for the clearance of triglycerides during the postprandial period (41,42). LSR heterozygous mice display increased postprandial triglyceride levels, decreased clearance of lipid particles, and increased levels of proatherogenic lipoproteins following a Western diet (35).…”
Section: Discussionmentioning
confidence: 99%
“…Genes lying at the 10 Mb region in humans that encompasses the point of maximum linkage evidence in baboons (HSA19q12-q13.12) include at least one with potential effects on LDL catabolism. LSR/LISCH7, the lipolysis-stimulated lipoprotein receptor, codes for a receptor that is differentially stimulated by free fatty acids of different chain lengths and is able to bind apoB-and apoE-containing lipoproteins (41). Furthermore, LSR is hypothesized to be an alternate pathway of LDL clearance in the liver separate from the LDLR or the LDL-receptor related protein (LRP) pathways (42).…”
Section: Discussionmentioning
confidence: 99%